Normal hearing function genetics: have you heard all about it? An integrated approach of genome-wide association studies and transcriptome-wide association studies in three Italian cohorts - Santin, Aurora; Pianigiani, Giulia; Gialluisi, Alessandro; Pecori, Alessandro; Spedicati, Beatrice; Costanzo, Simona; Persichillo, Mariarosaria; Bracone, Francesca; Nardone, Giuseppe Giovanni; Tesolin, Paola; Lenarduzzi, Stefania; Morgan, Anna; et al. (Frontiers in Genetics, 2025)
IntroductionDeepening the genetic mechanisms underlying Normal Hearing Function (NHF) has proven challenging, despite extensive efforts through Genome-Wide Association Studies (GWAS).MethodsNHF was described as a set of nine quantitative traits (i.e., hearing thresholds at 0.25, 0.5, 1, 2, 4, and 8 kHz, and three pure-tone averages of thresholds at low, medium, and high frequencies). For each trait, GWAS analyses were performed on the Moli-sani cohort (n = 1,209); then, replication analyses were conducted on Carlantino (CAR, n = 261) and Val Borbera (VBI, n = 425) cohorts. Expression levels of the most significantly associated genes were assessed employing single-nucleus RNA sequencing data (snRNA-seq) on human fetal and adult inner ear tissues. Finally, for all nine NHF traits, Transcriptome-Wide Association Studies (TWAS) were performed, combining GWAS summary statistics and pre-computed gene expression weights in 12 brain tissues.ResultsGWAS on the Discovery cohort allowed the detection of 667 SNPs spanning 327 protein coding genes at a p < 10−5, across the nine NHF traits. Two loci with a p < 5 × 10−8 were replicated: 1. rs112501869 within SLC1A6 gene, encoding a brain high-affinity glutamate transporter, reached p = 6.21 × 10−9 in the 0.25 kHz trait. 2. rs73519456 within ASTN2 gene, encoding the Astrotactin protein 2, reached genome-wide significance in three NHF traits: 0.5 kHz (p = 1.86 × 10−8), PTAL (p = 9.40 × 10−9), and PTAM (p = 3.64 × 10−8). SnRNA-seq data analyses revealed a peculiar expression of the ASTN2 gene in the neuronal and dark cells populations, while for SLC1A6 no significant expression was detected. TWAS analyses detected that the ARF4-AS1 gene (eQTL: rs1584327) was statistically significant (p = 4.49 × 10−6) in the hippocampal tissue for the 0.25 kHz trait.ConclusionThis study took advantage of three Italian cohorts, deeply characterized from a genetic and audiological point of view. Bioinformatics and biostatistics analyses allowed the identification of three novel candidate genes, namely, SLC1A6, ASTN2, and ARF4-AS1. Functional studies and replication in larger and independent cohorts will be essential to confirm the biological role of these genes in regulating hearing function; however, these results confirm GWAS and TWAS as powerful methods for novel gene discovery, thus paving the way for a deeper understanding of the entangled genetic landscape underlying the auditory system.